Strategi Pemasaran UMKM di Masa Pandemi Covid-19: Studi Kasus UMKM di Kawasan Pondok Pesantren Darul 'Ulum Jombang - Mas’adah; Asngadi; Agung Hirmantono (Penerbit Goodwood, 2021)
Purpose: This study aims to determine the marketing management strategies of MSME players during the Covid-19 pandemic. This research is included in qualitative research with a case study approach. Research Methodology: The data obtained in this study were qualitative data collected through in-depth interviews, observation and documentation—retrieval of informants using a purposive sampling technique. The source of the data came from 4 MSME informants who trade in the Islamic boarding school area. The informants have been trading in this micro-business sector for at least five years as their main job. The data were analyzed using interactive analysis techniques, namely through the stages of data reduction, data presentation, and drawing conclusions and verification. Results: The result of this research is that the strategy undertaken by MSME actors is to strengthen and expand the network of customers in collaboration with Kyai or Islamic boarding school Teachers by doing